The Relationship between Family Support and the Quality of Life of Elderly Patients with Diabetes Mellitus in the Working Area of the Dungingi Health Center - Rhevalina Pricilia Suleman; Rona Febriyona; Inne Ariane Gobel; Andi Safutra Suraya (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The elderly experience changes in the endocrine system that are associated with a decrease in insulin production by the pancreas and insulin resistance that causes the degenerative disease diabetes mellitus, this affects the emotional well-being of the sufferer, which leads to a decrease in the quality of life, therefore the family as a support system that provides direct care for the sick elderly is very important in improving the quality of life of the elderly. This study aims to find out how the relationship between family support and the quality of life of the elderly with diabetes mellitus (DM) in the working area of the Dungingi Health Center. The quantitative method with the research design used in this study is cross sectional where samples are selected through the purposive sampling method, the sample number is 36 elderly respondents with DM in the working area of the Dunging health center. The results showed that the majority of respondents had less family support of 26 people (72.2%), moderate quality of life of 22 people (61.1%). Statistical values are obtained by Asymp. sig (2 tailed) p value of 0.029 < 0.05 which means that there is a relationship between family support and the quality of life of elderly people with diabetes mellitus in the working area of the dungingi health center. Family support is essential in improving the quality of life in the elderly with DM.